One nation, underprivileged : why American poverty affects us all - Rank, Mark R. (Oxford University Press, 2004)
"Mark Robert Rank shows that the fundamental causes of poverty are to be found in our economic structure and political policy failures, rather than individual shortcomings or attitudes. He establishes for the first time that a significant percentage of Americans will experience poverty during their adult lifetimes and ... demonstrates that poverty is an issue of vital national concern"--Jacket